Anatomical-based diagnosis and filler injection techniques: marionette line (static labiomandibular fold) - Gi-Woong Hong; Sky Wong; Song-Eun Yoon; Jovian Wan; Kyu-Ho Yi (Journal of Dermatological Treatment)
Purpose Marionette lines, also known as static labiomandibular folds, are common age-related perioral wrinkles that impact facial aesthetics, particularly in Asian populations. This article aims to examine the anatomical basis, etiology, and filler injection techniques used for treating marionette lines.Materials and Methods The study reviews anatomical studies and clinical practices related to marionette lines. Anatomical observations focus on the position of the modiolus and its relationship to age-related changes. Treatment approaches are examined through a review of filler injection techniques, including supramuscular and submuscular fat layer targeting, as well as neurotoxin use for enhancing treatment outcomes.Results The review finds that the anatomical positioning of the modiolus in Asian populations predisposes them to increased susceptibility to commissural ptosis and wrinkle formation. Filler injections, particularly using a cannula for deeper layers, are effective for addressing volumetric loss in the supramuscular and submuscular layers. Neurotoxin injections into the depressor anguli oris muscle can enhance results by reducing downward force on the oral commissure.Conclusions Marionette lines are complex, multifactorial wrinkles that benefit from a multimodal treatment approach, combining dermal fillers and neurotoxins. Awareness of anatomical variations and proper injection techniques is crucial for achieving optimal aesthetic outcomes and minimizing risks.